Implementasi Pengembangan Manajemen Sumber Daya Pendidikan Islam dalam Meningkatkan Kualitas Lembaga Pendidikan - Buyung Buyung; Musyarapah Musyarapah (Educational Journal, 2026)
This study aims to analyze the implementation of Islamic educational resource management development in improving the quality of educational institutions. Educational resources include teaching staff, administrative staff, students, and facilities and infrastructure, which are managed systematically and sustainably. The research method used was a qualitative approach. The results indicate that the implementation of Islamic educational resource management development is carried out through strategic planning, effective organization, implementation of competency improvement programs, and ongoing evaluation. Strengthening Islamic values ​​in every aspect of management is also a crucial factor in shaping a superior character and organizational culture. Furthermore, visionary leadership and the active participation of all school members contribute to improving the quality of educational institutions. With optimal resource management, Islamic educational institutions are able to improve the quality of educational services, increase competitiveness, and produce competent and virtuous graduates. Therefore, the development of Islamic educational resource management needs to be carried out sustainably to address the challenges of education in the modern era.